Evaluating the doormat creating life skill program in the Cahaya Kahuripan Bangsa Community Learning Centre Lembang - Lince Sari Dianawati Leatemia; Aldian Hudaya (IKIP Siliwangi Bandung, 2018)
Non-formal education involves the Paket program, which the Cahaya Kahuripan Bangsa Community Learning Centre deems insufficient in supporting their learning community’s needs and the demands of the society. For that purpose, the community learning centre conducts a lifeskill training program in creating doormats. This study aims to evaluate the said program using Stufflebem’s CIPP model, gathering data from interviews, literary studies and observations. While generally showing that each aspect falls into the good category, the results also showed several factors that support and hinder the program. Among those are the participants’ motivation, support from the business world, and managerial-related issues. In general, this program has been performing as it intends itself to do.